UNDERSTANDING AS BASIC PREMISE OF CROSS-CULTURAL COMMUNICATION: PSYCHOLINGUISTIC AND SOCIO CULTURAL ASPECTS - K. L. Kabakhidze (Концепт: философия, религия, культура, 2017)
The author of the article analyzes cross-cultural communication from social philosophy viewpoint defining invariant features of cross-cultural communication based on dialogue (Mikhail Bakhtin) and dialect nature of human communication. Theoretical description of the nature of crosscultural communication is illustrated by live examples of cultural conflicts borrowed from the history of the Russian diplomacy. Since consciousness has the communicative origin, whereas cross-cultural understanding is rooted in neuropsychological aspects of cognition, antinomy of “sign-symbol”, the article depicts the mechanisms of speech production and speech perception divided between the strata of consciousness and cognition. The paper underlines the hermeneutic essence of intercultural dialogue, which reveals through understanding between communicators at conceptual and semantic levels, moreover at cultural and civilizational dimensions in the context of the multipolar world, taking into account global socioeconomic, ethnocultural, political trends in different countries around the world. Internalization of education, information and telecommunication technologies catalyzes intercultural communication, forming knowledge society inhabited by ‘homo loquens’. Intensive intercultural contacts quite often give rise to cultural conflicts. The author categorizes this phenomenon by ranging the mistakes, insufficient understanding, embarrassments and conflicts of intercultural communication, reveals in-depth socio-cultural paradigm, axiological, world outlook and religious aspects that cause negative outcomes of intercultural contacts. Understanding in intercultural dialogue is composed of ethnosociocultural context and psycholinguistic mechanisms of speech perception and speech production. The operational item of understanding is considered to be a code which has a symbolic nature. The article depicts the interconnection between symbol, code, act of communication, consciousness and national world view.